Autologous Fat Grafting and the Occurrence of Radiation-Induced Capsular Contracture. Issue 3 (May 2021) - Martin, Shanique; Cai, Lawrence; Beniwal, Amit; Tevlin, Ruth; Lee, Gordon; Nazerali, Rahim S.
Abstract : Introduction: Radiation therapy is a known risk factor for capsular contracture formation after implant-based breast reconstruction. Although autologous fat grafting (AFG) has been shown to reverse radiation-induced tissue fibrosis, its use as a prophylactic agent against capsular contraction has not been assessed in the clinical setting. In the setting of 2-stage implant-based reconstruction and postmastectomy radiation therapy, we explored the effect AFG has on the prevalence of capsular contracture. Materials and Methods: A retrospective chart review of patients who underwent immediate tissue expander (TE) placement followed by postmastectomy radiation therapy and secondary implant-based reconstruction at our institution between January 2012 and December 2019 was performed. Patients were divided into 2 cohorts based on whether or not AFG was performed at the time of secondary reconstruction. The primary outcome of interest was the occurrence of capsular contracture after TE exchange. Results: Overall 57 patients (57 breasts) were included, 33 of whom received AFG at the time of TE exchange. All but 1 patient underwent submuscular implant placement, and the mean follow-up was 1.96 years. There was no significant difference in the prevalence of medical comorbidities between the study groups. Capsular contracture occurred in 24 patients (42.1%). Seventeen of these patients had undergone AFG at the time of TE exchange (17/33 patients, 51.5%), and 7 of these patients had not (7/24 patients, 29.2%). Most of the capsular contracture cases were Baker grades III or IV (14 patients, 58.3%), and 50% of patients with capsular contracture of any grade ultimately required operative intervention. Multivariate logistic regression analysis demonstrated that AFG did not significantly influence the occurrence or severity of capsular contracture, or did not impact the need for operative intervention in this patient population. Conclusions: Implant-based reconstruction of the irradiated breast is associated with high postoperative capsular contracture rates. Although AFG has shown promise in reversing radiation-induced dermal fibrosis, no protective effect on the development of capsular contracture after stage 2 reconstruction was observed in this study population. Further investigation in the form of randomized, prospective studies is needed to better assess the utility of AFG in preventing capsular contracture in irradiated patients. Abstract : Supplemental digital content is available in the text.